Ozone field and monsoon rainfall - ALI, HAMID (MAUSAM, 1990)
Ozone field over Indian stations for good monsoon years and bad monsoon/drought years has been studied. It is noticed that (i) ’total ozone’ maxima in the bad monsoon/drought year has a higher value than in the preceding/ensuing good monsoon year and (ii) the concentration of ozone in the IVth ozone layer (1.9.2-23.7 km) for the month of April is higher for the bad monsoon/drought year than for the preceding/ensuing good monsoon year.